Belas Kasih Allah dalam Kematian Kristiani Menurut Karl Rahner - Pradipta, Nemesius (Jurnal Teologi (Journal of Theology), 2019)
Death is a definite and inevitable reality of life. Every human being will be faced with the reality of death regardless of the circumstances of their lives. Karl Rahner assumes that in a Christian perspective the reality of death must be interpreted in its union with God's own love shown through the death and resurrection of His Son, Jesus Christ. Death in Karl Rahner's thought is based on God's giving (Selbstmitteilung Gottes) which appears in the death and resurrection of Jesus Christ to redeem mankind from sin and death. The death of Christ has changed the meaning of human death no longer as a punishment for sin, but as participation in the love of God who wants to save human beings.